Ambedkar: Pioneer of Education in India - Khosla, Dr. Sunil (Innovative Research Thoughts, 2017)
The philosophy of Baba Saheb is targeted towards the practical realisation of human potential, and is significant in the modern times. Education, in Ambedkar's view, should be seen as a movement. If it does not accomplish what it set out to achieve, then it is pointless. A genuine education nurtures humanity, creates opportunities for making a living with dignity, teaches us valuable lessons of life, and instils in us a sense of equality. His qualifications as a thinker is exhibited in essays, books, periodicals, and newspapers that he authored during his lifetime. The Problem of the Rupee, Provincial Finance in British India, Annihilation of Caste, and Shudras were some of the works having relevance in the contemporary society. Ambedkar had the belief that the best way to improve people's standard of life was via the dissemination of knowledge. "Educate, unite, and fight" was the motto he used. The concepts of human dignity and respect for oneself were at the core of his philosophy. He believed that education was the key to bringing about social change that would bring about justice, equality, brotherhood, freedom, and an absence of fear. He advocated for the establishment of a society that was guided by moral principles. It should go without saying that the best way to spread these moral principles is through education.